2018
DOI: 10.1145/3161166
|View full text |Cite
|
Sign up to set email alerts
|

hEYEbrid

Abstract: We introduce hEYEbrid, a calibration-free method for spontaneous and long-term eye gaze tracking, with competitive gaze estimation. It is based on a hybrid concept that combines infrared eye images with corneal imaging. For this, two eye cameras are mounted on a glasses frame. In this way, the pupil can be tracked quickly with high precision. This information is translated into the corneal image, which is used to create a connection to the environment, acting like a scene camera. In a user study with 20 partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…It was able to improve a detected inaccuracy of 2.64 • to 1.01 • . Accuracies of 1 • are considered good results [Lander et al 2018], even if greater results are often reported in controlled environments for remote eye trackers [Feit et al 2017;Nyström et al 2013].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was able to improve a detected inaccuracy of 2.64 • to 1.01 • . Accuracies of 1 • are considered good results [Lander et al 2018], even if greater results are often reported in controlled environments for remote eye trackers [Feit et al 2017;Nyström et al 2013].…”
Section: Discussionmentioning
confidence: 99%
“…Accuracy is evaluated in degrees of visual angle and computed by the difference in position between two paired points (gaze and target), and comparing it with a desired target accuracy. A predefined accuracy threshold of 1.5 • was set for the evaluation of the method, as remote trackers' average accuracy is often found to be larger than 1 degree [Feit et al 2017;Lander et al 2018].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nakazawa et al [22] propose a gaze-tracking algorithm based on the CIS using a bendable LED dot matrix system assisted by an infrared camera. Lander et al [23] propose a work for computing 3D gaze from the 2D gaze with the help of infrared cameras and scene cameras. Ohshima et al [24] try to match the CI with the scene pictures in the database by neural network, showing the possible privacy security risk and the prospect of human-machine interaction for CIS.…”
Section: The Cis Researches and Applicationsmentioning
confidence: 99%